Fracture toughness of cancellous iliac bone - Calin-Daniel Stefan; Liviu Marsavina; Catalin-Adrian Miu (Open Veterinary Journal)
Background: Cancellous bone mechanical properties are directly linked to the structural integrity, which is a result of bone quantity, the quality of its bone matrix and its microarchitecture. Several studies highlighted the bone behavior under specific loads, contributing to understanding risk factors and developing more effective therapeutic strategies. The anatomy and stability of iliac bone fractures, providing insight into pelvic trauma management.